Tantangan Nasional untuk Menghadapi Globalisasi - Sulistyanto . (JURNAL CITRA WIDYA EDUKASI, 2018)
Humans want to live together help each other, mutual assistance, and mutual respect that is expected with better education, ie the quality of education. Globalization contains various contradictions by John Naisbitt, are: 1) The global culture as opposed to the local culture; 2) Univesal opposite with individual; 3) Traditional opposite to modern; 4) Long-Term opposite to short-term; 5) The competition contrary to the equal opportunities; 6) Limited human intellect opposite to the explosion of science and technology; and 7) Spiritual opposite to material. The idea of ​​"Global Governance" due to concerns about the earth's humans that require maintenance so that balanced development. Globalization accelerated with the remarkable growth of the mass media by telecommunications considered eliminating geographic boundaries of the country. The threat of globalization but nationalism is not largely determined by its internal problems are of political, economic, social, cultural, defense and homeland security. Pancasila ideology that leads us to improved ways of thinking in general, think in the human psyche that is good at sorting Indonesia which are compatible with national character names and which are not appropriate.